Kondisi Kualitas Data Debit Sungai Tahun 2015-2016 di Indonesia - Sri Mulat Yuningsih (Jurnal Sumber Daya Air, 2019)
River discharge data in Indonesia has been published since 1909 with number of hydrologic stations relatively increasing but conditions of quality were decreasing. The quality of discharge data has become a key issue in the field of hydrology. Research and Development Center for Water Resources has developed a method of one year hydrological data quality control for the period of 2014 – 2018. The purpose of this study was to provide quality overview of discharge data and technical recommendation for improvements which need to be made. Discharge data quality control model consists of station condition, rating curve, water level data, and daily discharge data . The results of station conditions obtained from 14 gauging stations were categories as: 7 Good, 5 Poor, and 2 Bad. Analysis of rating curve were carried out on 840 stations, result shows 299 stations with categories of Good for 11 stations and Poor for 288 stations. Analysis of water level data in 2016 of 651 stations shows resulted 16 Good, 351 Poor and 284 Bad. The results of daily discharge were 5 stations good categories and 179 poor. The application of quality control was made applicable with an assessment that has been completed with clear and easily understood information. Recommendations for improvement that need to be carried out easily and on target can be identified based on the RADAR diagram.